Morphology of labourers of the Aluminium Works "Konin" as compared to other groups of physical workes - Puch, Alicja E.; Wąsalska, Aleksandra (Anthropological Review, 1978)
The purpose of this paper is to evaluate morphological diversity of physical workers performing various types of proffesional activity, with special attention paid to the employees of Aluminium Works Konin. Numerical data on morphology were taken from the literature as well as from authors’ own survey. Diversity of morphological characters was evaluated with use of multivariate analysis — the Penrose's method. The most frequently observed body dimensions were chosen for the present study — for parameters of distributions of these characters in various proffesional groups, see table 1. Statistical significance of Penrose's distances was estimated by the chi-square test on the 0,05 level. It was shown that multivariate distances between all proffesional groups insignificantly differ from zero. Hence, in accordance with the premises of the method applied it should be concluded that there are no morphological differences between analysed groups. Therefore the authors suggest that there is no particular type of body build for individuals performing certain type of physical work and there is no such a thing as morphological selection of workers for a given type of proffesional activity.